The untold story: Teaching cases and the rise of international business as a new academic field - Amdam, Rolv Petter; Benito, Gabriel R. G.; Grøgaard, Birgitte (Journal of International Business Studies, 2023)
The dominant narrative about the rise of international business (IB) focuses on early research and the institutionalization of a new academic field. In this study, we explore the role of case writing in the field’s formative period from the mid-1950s to the mid-1960s. Based on an analysis of teaching cases on IB topics, we demonstrate that case-based teaching, including the writing of cases, was an innovative pedagogical method that made a strong impact on the formation of the new academic field. Analyzing the cases and the background and affiliation of their authors offers new insights into the linkages to other disciplines from which the new academic field emerged. The analysis of the cases also provides new insight into how the case authors connected to the new practical experiences from an increasing number of multinational enterprises, particularly from the US, and conceptualized the experiences into a pedagogical language. The investigation covers 489 cases written by scholars located in 18 countries from the early 1950s to 1963, as well as archival studies of the business schools and institutions that initiated the production of cases.